2019
DOI: 10.1126/sciadv.aau9784
|View full text |Cite
|
Sign up to set email alerts
|

Stress inversions to forecast magma pathways and eruptive vent location

Abstract: When a batch of magma reaches Earth’s surface, it forms a vent from which volcanic products are erupted. At many volcanoes, successive batches may open vents far away from previous ones, resulting in scattered, sometimes seemingly random spatial distributions. This exposes vast areas to volcanic hazards and makes forecasting difficult. Here, we show that magma pathways and thus future vent locations may be forecast by combining the physics of magma transport with a Monte Carlo inversion scheme for the volcano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 38 publications
5
81
0
Order By: Relevance
“…It is a good proxy of the ground surface extension, which may eventually lead to an increase in the secondary permeability by fracturing and hence of degassing and, in extreme cases, to the opening of new volcanic vents/ fissures. Numerical models and experimental studies showed that dyke propagation is influenced by the local properties of the stress field and by preexisting fractures (Gaffney et al 2007;Maccaferri et al 2011;Le Corvec et al 2013;Corbi et al 2015Corbi et al , 2016Rivalta et al 2019). For the specific case of Campi Flegrei, the maps indicate that the maximum horizontal displacements are located over a semicircular annular region, with a radius of about 2-3 km from the town of Pozzuoli.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is a good proxy of the ground surface extension, which may eventually lead to an increase in the secondary permeability by fracturing and hence of degassing and, in extreme cases, to the opening of new volcanic vents/ fissures. Numerical models and experimental studies showed that dyke propagation is influenced by the local properties of the stress field and by preexisting fractures (Gaffney et al 2007;Maccaferri et al 2011;Le Corvec et al 2013;Corbi et al 2015Corbi et al , 2016Rivalta et al 2019). For the specific case of Campi Flegrei, the maps indicate that the maximum horizontal displacements are located over a semicircular annular region, with a radius of about 2-3 km from the town of Pozzuoli.…”
Section: Discussionmentioning
confidence: 96%
“…Blue dots mark the RIM virtual displacement locations, along elliptic arcs. UTM WGS84, Zone 33 N coordinate system (m) 3D deformation field can help to constrain the expected radial distance of eruptive vents from the center of the caldera, and large values of horizontal deformation can be used as a spatial precursor to future vent opening (see Bevilacqua et al 2015Bevilacqua et al , 2017Rivalta et al 2019;Patra et al 2019).…”
Section: Deformation Boundariesmentioning
confidence: 99%
“…In order to understand why the sill turned as observed, before proceeding with a 3D simulation, we reduce the physics of this problem to its component parts and evaluate how these affect the sill's direction of propagation. Previous studies have found that dyke trajectories are dependent on the ratio of tectonic to topographic loading stresses 3,6,7 . Here we propose that contrasting magma and rock weight gradients (buoyancy) must also be considered as one of the dominant forces.…”
Section: Parameters and Numerical Resultsmentioning
confidence: 97%
“…One such model (Mastin et al, 2008) was even used during the 2004-2008 eruption of Mount St. Helens to forecast the final volume of the eruption (Mastin et al, 2009), and a volcano-like chamber-conduit model was used to forecast the duration of the Lusi mud eruption in Indonesia (Rudolph et al, 2011). Models of magma transport that account for a volcano's stress history can even forecast the location of future eruptive vents (Rivalta et al, 2019).…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%